Penerapan Media Mading Bahasa Teks Ceramah (MAHATERA) Terhadap Kemampuan Keterampilan Menulis Teks Ceramah - Anggraini, Suhesti; Khaerunnisa, Khaerunnisa (BELAJAR BAHASA: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to improve students' lecture text writing skills through the application of Mahatera media (Mading Bahasa Teks Ceramah) in Indonesian language learning. This study is a Classroom Action Research (CAR) conducted in class XI SMK Muara Ilmu with 25 students. The study was conducted in two cycles, each consisting of four stages, namely: planning, implementation of actions, observation, and reflection. Data collection techniques used observation, interviews, documentation, and lecture text writing skills tests. The results of the study showed that the application of Mahatera media (Mading Bahasa Teks Ceramah) can significantly improve students' lecture text writing skills. The average score of SMK Muara Ilmu students in the pre-cycle stage obtained an average score of 47, in the cycle II stage with an average score of 70 and in the cycle II with an average score of 85. The ability of writing lecture text skills in grade XI students in the pre-cycle learning stage was lacking and did not achieve completeness above the KKM, the learning stage of cycle I experienced an increase of 36% from 8%, and in the learning stage of cycle II there was an increase of 92% from the pre-cycle stage to the cycle II stage. In addition, students showed increased enthusiasm, active participation, and thinking skills in organizing systematic lecture content, using persuasive language, and developing creativity in the wall magazine media. Thus, the Mahatera media (Language Wall Magazine Text Ceramah) has proven effective in improving the skills of writing lecture texts and is worthy of being used as an alternative interactive learning media in learning Indonesian.